TARI SANGHYANG: MEDIA KOMUNIKASI SPIRITUAL MANUSIA DENGAN ROH - I Nyoman Lodra (Harmoni, 2017)
Sanghyang Dance is synonymous with "trance" as an expression of unity between "atman" and the "spirit" deliberately invited to enter into the human body. Media such as offerings, sacred chants (songs), the orchestra, and dancers, are prepared through the ritual procession for this dance. The dance in a "trance" has the ability beyond the norm of human in spiritual communications that havedeveloped in Bali ethnic society since prehistoric times. Spiritual communication is interpreted as inner dialogue between human and spirits. To understand this phenomenon in-depth,a research entitled "Sanghyang Dance: spiritual communications between humanand spirits through anthropology and sociology of art approaches"has been done. The focus of the study is a form of spiritual communication between human and spirits, and the existence of sanghyang dance in Balinese society. The aim of research is to determine and describe the form of spiritual communication between human and spirits, and to determine the existence of sanghyang dance in Balinese society. The findings of this study are expected to add knowledge about spiritual communications betweenhuman and spirits. Themethod of the study is qualitative and descriptive. The data collection methods include observation, interviews and document collection. The data were analyzed using ethnographic, social exchange theory, and the theory of hegemony. The results of this study are human beings need the presence of the spirits to overcome the problems in lives while sanghyang dance performance is already scarce in Bali.